DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN BURNOUT PADA METODE PEMBELAJARAN JARAK JAUH MAHASISWA FAKULTAS KEDOKTERAN - Elsa Elvina (2021)
Distance education (online learning) makes college students felt unfamiliar with this changes, also the lack of preparation for dealing with this new method of study. The appearance of boredom causes by exhausted. this condition as known as burnout. Medical students are more susceptible to encounter the pressure. Social network, including family, classmates, and best friends are the most important factors of psychocial that have the biggest effect on student to reach their achievement in distance education method. Somebody will solve their problem on their own environment. This study aim to determine the difference between social support from friends with the burnout of distance education method of Faculty of Medicine Student 2020. This research uses an observational analysis, cross sectional study approach, using a modified questionnaire from previous studies. Sampling was 92 respondents using stratified random sampling technique. Unpaired T-test table data can have a probability > 0.05. The burnout for distance education method does not have a significant social support from friends.